2020
DOI: 10.1139/cjps-2019-0241
|View full text |Cite
|
Sign up to set email alerts
|

An electrochemical advanced oxidation process (EAOP) for the inactivation ofRhizoctonia solaniin fertigation solutions

Abstract: Boron-doped diamond anodes and stainless-steel cathodes were employed in an electrochemical flow cell and evaluated for inactivation efficacy on the plant pathogen Rhizoctonia solani J.G. Kühn [Thanatephorus cucumeris (A.B. Frank) Donk] in hydroponic fertigation water. The electrochemical system showed promise as an electrochemical advanced oxidation process (EAOP) in that significant reductions in R. solani (AG-8) were achieved; however, to achieve complete inactivation the system required supplemental chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Although F. oxysporum and R. solani can be killed at 14 mg L −1 for 6 min and 12 mg L −1 /L for 10 min contact time, respectively, phytotoxicity occurs [55]. Lévesque et al [2] demonstrated the inactivation efficacy of electrochemical disinfection in hydroponic irrigation water contaminated with mycelial suspensions of R. solani. Thereby, 1.14 mA cm −2 for a contact time of 6 min in the presence of fertilizer resulted a notable but not complete inactivation of R. solani.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although F. oxysporum and R. solani can be killed at 14 mg L −1 for 6 min and 12 mg L −1 /L for 10 min contact time, respectively, phytotoxicity occurs [55]. Lévesque et al [2] demonstrated the inactivation efficacy of electrochemical disinfection in hydroponic irrigation water contaminated with mycelial suspensions of R. solani. Thereby, 1.14 mA cm −2 for a contact time of 6 min in the presence of fertilizer resulted a notable but not complete inactivation of R. solani.…”
Section: Discussionmentioning
confidence: 99%
“…Water is a fundamental element in greenhouse crop production, but its availability is increasingly limited mainly due to climate change, overexploitation of aquatic ecosystems and contamination of water sources [1]. Irrigation systems in protected agriculture face the challenge of ensuring water supply and at the same time adapting to the needs of new legislative and social restrictions by governments that increasingly limit the amount of fresh water available for crop production [2][3][4]. A conscious handling and use of the resource water, especially its reuse, poses a challenge for farmers and gardeners to meet this demand.…”
Section: Introductionmentioning
confidence: 99%
“…This risk may not be tenable with many producers and a sterilization step may be required. However, it should be noted that several of the mineralization processes (e.g., ozonation, electrochemical oxidation) can achieve this goal [211][212][213].…”
Section: Phytotoxicity and Pathogenicitymentioning
confidence: 99%
“…Recent studies on electrochemical oxidation techniques have also been shown to inactivate pathogens while mineralizing organic matter in the hydroponic nutrient solution [212,213]. Although a wide variety of pathogen control techniques are available [219], the prospect of simultaneously managing pathogens and mineralizing organic matter makes ozonation and electrochemical oxidation technologies very appealing in the context of the current discussion.…”
Section: Treatment Of Nutrient Extractsmentioning
confidence: 99%